2015
DOI: 10.1175/jas-d-15-0008.1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in Marine Aerosols Revealed by 454 Pyrosequencing of the 16S rRNA Gene*

Abstract: Although bacteria are an important biological component of aerosol particles, studies of bacterial communities in remote marine aerosol are largely lacking. In this study, aerosol samples were collected over the western Pacific Ocean, the northern Pacific Ocean, the Arctic Ocean, and the Norwegian Sea during the Fifth Chinese National Arctic Research Expedition (CHINARE 5). The diversity and structure of aerosol bacterial communities, based on 454 pyrosequencing, were explored in these samples. The bacterial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…The average number of OTUs in our aerosol samples collected during springtime was similar to the number of OTUs in the Norwegian Sea and the Western Pacific in the summer and lower than OTUs in the Northern and Western Pacific Ocean in the fall [56]. Since seasonality impacts airborne bacterial abundance [12,19] and community composition [56], spatiotemporal variability of airborne microbes should be studied during other seasons to assess interannual variability in this region. The number of observed OTUs during non-storm conditions was lower than those measured in coastal cities in the Mediterranean during dust storms [31,58].…”
Section: Airborne Microbiome Above the Msmentioning
confidence: 56%
See 3 more Smart Citations
“…The average number of OTUs in our aerosol samples collected during springtime was similar to the number of OTUs in the Norwegian Sea and the Western Pacific in the summer and lower than OTUs in the Northern and Western Pacific Ocean in the fall [56]. Since seasonality impacts airborne bacterial abundance [12,19] and community composition [56], spatiotemporal variability of airborne microbes should be studied during other seasons to assess interannual variability in this region. The number of observed OTUs during non-storm conditions was lower than those measured in coastal cities in the Mediterranean during dust storms [31,58].…”
Section: Airborne Microbiome Above the Msmentioning
confidence: 56%
“…'Common' organisms found over the Mediterranean Sea in this study compared to five studies focusing on marine aerosols [1,8,38,55,56], five studies focusing on coastal aerosols [3,31,32,57,58], and six samples from one study focusing on Mediterranean surface seawater [59]. Columns under open ocean studies refer to references [1,8,38,55,56], columns under Mediterranean coastal studies refer to references [3,31,32,57,58], and columns under Mediterranean seawater samples refer to six samples from reference [59]. To quantitatively assess the diversity and estimate the differences in airborne bacterial communities over the MS, we report microbial community richness, expressed as the number of unique OTUs observed, and diversity expressed as Shannon's diversity index (H), estimated from the abundance of bacteria in each sample (Table 1).…”
Section: Airborne Microbiome Above the Msmentioning
confidence: 96%
See 2 more Smart Citations
“…Bioaerosol tend to be primarily bacteria and some fungal spores, although pollen (O'Connor et al, 2014) and possibly viruses (Griffin et al, 2001) have been reported. Some studies have performed DNA analysis of bioaerosol, reporting a wide diversity (Smith et al, 2012Xia et al, 2015).…”
mentioning
confidence: 99%